Melestarikan Budaya Jawa di Trans Melalui Makanan Tradisional - Egydia Slavina; Solfema Solfema; Lili Dasa Putri (Student Scientific Creativity Journal, 2025)
Javanese culture has a rich and diverse uniqueness, including in its traditional culinary aspects. Traditional food is not just a dish, but also a symbol of cultural values, customs, and local wisdom that have been passed down from generation to generation. However, in the era of globalization and modernization, traditional food faces major challenges due to shifts in people's consumption patterns who prefer fast food or international cuisine. This article discusses efforts to preserve Javanese culture through traditional food that not only aims to maintain cultural identity, but also to increase local economic empowerment. Using a literature study method, this study shows that strategies such as digitalization of promotion, product innovation, and tourism integration are able to revive interest in traditional food among the community. Thus, preserving traditional Javanese food can be one solution to maintain cultural heritage while creating sustainable economic opportunities